2015
DOI: 10.15406/bbij.2015.02.00043
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on the Use of Stability Parameters in Plant Breeding

Abstract: The phenotype of an individual depends upon both the genetic make-up and environmental influences. Genotype × environment interaction is considered as an important source of discrepancy in any crop, and different methods have been used to distinguish genotypes for their behavior in different environmental conditions. These constitute univariate parametric, such as environmental variance, regression slope, and deviation from regression, to multivariate methods. In this review, we summarize the priorities and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 83 publications
(94 reference statements)
1
24
0
Order By: Relevance
“…The phenotypic stability of the quantitative trait can be explored by the use of many of statistical methods allowing the analysis of genotype by environment interaction. However, these methods may produce different results (Fasahat et al 2015). The first one was AMMI (additive main effects and multiplicative interaction) analysis (Gauch 2006), which is widely used in stability analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic stability of the quantitative trait can be explored by the use of many of statistical methods allowing the analysis of genotype by environment interaction. However, these methods may produce different results (Fasahat et al 2015). The first one was AMMI (additive main effects and multiplicative interaction) analysis (Gauch 2006), which is widely used in stability analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies as indicated by high ecovalences the strongest response to different environmental conditions by tree height showed P. balsamifera × P. trichocarpa hybrid, the weakest showed P. deltoides × P. nigra. Ecovalence shows how strongly varies genotype response to different environmental conditions of treatments or, in other words, the ecovalence of the genotype is its interaction with the environments (Fasahat et al 2015). Ecovalence characterizes the relative lability of a population in relation to other populations and describes what part of the G × E interaction is determined by ecogenetic variability of a hybrid.…”
Section: Performance Of Different Poplar Hybrids Under the Stressors mentioning
confidence: 99%
“…Typically, a significant G × E exists whenever the genotype performance greatly differs with environments 2 , 3 . When a significant G × E is identified, subsequent stability analysis is often carried out to identify stable genotypes which exhibit consistently higher yield over several environments 4 . The presence of significant G × E has been found in growth and yield traits of several field 5 8 and vegetable crops 3 , 9 11 .…”
Section: Introductionmentioning
confidence: 99%